Recuros didácticos virtuales ajustados a procesos metodológicos para el desarrollo del pensamiento lógico matemático en los niños de 5 a 6 años de la unidad educativa " Vicente León" - Molina Guzmán, Clara Doris (2022)
This research aims to promote the development of mathematical logic in school-level children, and analyze their influence on learning process through virtual playful activities for five-year-old’s children at Unidad Educative Vicente León. The methodology used in this research is non-experimental. It was based on scientific information. It collected real data base about the issue using research tools. This process ensured an appropriate study and the feasibility of applying the methodology. Also, this investigative work collected all adequate and necessary bibliography used for research purposes. The research process included an analysis and interpretation of the data with an objective vision. After the execution of the didactic proposal for the development of mathematical logical skills in children of High School sublevel, information reports favorable results. It made possible to check the alterations in the processes of logical learning, so it is important to apply methodological strategies based on the stimulation of the development of mathematical logic from an early age, which directly favors the children. Therefore, the research conclude that it is essential for teachers to be able to have virtual digital tools, which allow them to enhance teaching-learning processes in a safe way and to obtain favorable results in the integral improvement of children.